Silicone adhesive multilayer foam dressings as adjuvant prophylactic therapy to prevent hospital‐acquired pressure ulcers: a pragmatic noncommercial multicentre randomized open‐label parallel‐group medical device trial. (1st July 2021) - Beeckman, D.; Fourie, A.; Raepsaet, C.; Van Damme, N.; Manderlier, B.; De Meyer, D.; Beele, H.; Smet, S.; Demarré, L.; Vossaert, R.; de Graaf, A.; Verhaeghe, L.; et al.
Summary: Background: Silicone adhesive multilayer foam dressings are used as adjuvant therapy to prevent hospital‐acquired pressure ulcers (PUs). Objectives: To determine whether silicone foam dressings in addition to standard prevention reduce the incidence of PUs of category 2 or worse compared with standard prevention alone. Methods: This was a multicentre, randomized controlled medical device trial conducted in eight Belgian hospitals. At‐risk adult patients were centrally randomized ( n = 1633) to study groups based on a 1 : 1 : 1 allocation: experimental groups 1 ( n = 542) and 2 ( n = 545) – pooled as the treatment group – and the control group ( n = 546). The experimental groups received PU prevention according to hospital protocol, and a silicone foam dressing on the relevant body sites. The control group received standard of care. The primary endpoint was the incidence of a new PU of category 2 or worse at the studied body sites. Results: In the intention‐to‐treat population ( n = 1605), PUs of category 2 or worse occurred in 4·0% of patients in the treatment group and 6·3% in the control group [relative risk (RR) 0·64, 95% confidence interval (CI) 0·41–0·99, P = 0·04]. Sacral PUs were observed in 2·8% and 4·8% of the patients in the treatment group and the control group, respectively (RR 0·59, 95% CI 0·35–0·98, P = 0·04). Heel PUs occurred in 1·4% and 1·9% of patients in the treatment and control groups, respectively (RR 0·76, 95% CI 0·34–1·68, P = 0·49). Conclusions: Silicone foam dressings reduce the incidence of PUs of category 2 or worse in hospitalized at‐risk patients when used in addition to standard of care. The results show a decrease for the sacrum, but no statistical difference for the heel and trochanter areas.